Bentuk Kaki Berhubungan dengan Keseimbangan Fungsional pada Pasien Neuropati Diabetik - Ria Desnita; Debie Dahlia; Lestari Sukmarini (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Changes in foot posture in diabetic neuropathy patients affects the function of the legs as the base support in maintaining body balance. The study aimed to determine the correlation foot posture with functional balance in patients with diabetic neuropathy. This study design was analytic cross sectional, recruited 132 diabetic neuropathy patients. Statistical analysis used Chi Square, Pooled T-test, and multiple logistic regression. The results showed a significant correlation between foot posture and functional balance in diabetic neuropathy patients, the power of correlation is moderate and positive direction (p= 0.001; Î±= 0.05; r= 0,352). This study suggests the nurse to perform early detection and prevention of the risk of falls in diabetic neuropathy patients related to changes in foot posture and functional balance.